(3ePGcQI GdJMQjQs - (3LdGd GdOjf eMeO Hf YHO Gddg Hf eYQhas; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s ((3eMeO Hf Ydi Hf efUhQ Hf MejQ s)
(3ChdgG (B:s
(3cJGH GdWgGQI , HGH CfhGY GdWgGQI s
(3BNQgG (B:s
(3jfJgi HBNQ CHhGH GdQVGY , hBNQ eG ajg (B: (3hEf JRhL ChdkG HGdebQ HgG Ke HGdebQ , cGf fcGM GdChdi UMjMkG Ohf GdKGfjI s
(3HgG fXGe GdJYbjHIs
(3HQSe GdCejQ SdjeGf Hf gjLGf Hf GdbGSe GdMeRis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3abg GdePGgH GdCNQis